2021
DOI: 10.1039/d1ra05068k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical evaluation of the performance of IRMOFs and M-MOF-74 in the formation of 5-fluorouracil@MOF

Abstract: Drug delivery systems are a viable resource to be used in medical treatments that tend to be very aggressive to patients, increasing the bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The Mg-MOF-74 was synthesized using its established solvothermal procedure. , It is also noted here that many of the physiochemical properties of Mg-MOF-74 can be found elsewhere. The combined curcumin and ibuprofen loadings were impregnated onto Mg-MOF-74 using the wet-impregnation technique detailed in our earlier works (Figure ). ,, Briefly, the desired amount of drug was dissolved in 20 mL of MeOH via sonication for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Mg-MOF-74 was synthesized using its established solvothermal procedure. , It is also noted here that many of the physiochemical properties of Mg-MOF-74 can be found elsewhere. The combined curcumin and ibuprofen loadings were impregnated onto Mg-MOF-74 using the wet-impregnation technique detailed in our earlier works (Figure ). ,, Briefly, the desired amount of drug was dissolved in 20 mL of MeOH via sonication for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Drug-delivery systems (DDSs) can be used to reduce the side effects, provide controlled release, and selectively target cancer-related diseases. Metal–organic frameworks (MOFs) have become promising candidates as DDSs due to their well-defined structures, tunable pore size, high surface area, high loading/release of guest compounds, amphiphilic internal microenvironment, and pH-dependent degradation under simulated physiological conditions. For example, the organic ligand 1,1′-biphenyl-4,4′-dicarboxylic acid (BPDC) has produced various porous frameworks: UiO-67 (Zr), UiO-67-(NH 2 ) 2 (Zr), bio-MOF-1 (Zn), and BPDC-Zr. ,, These materials have been employed as carriers for the intracellular delivery of chemotherapeutic agents such as pemetrexed, 5-fluorouracil (5-FU), and Ru-90, and other pharmaceutical compounds such as brimonidine, calcein, and α-cyano-4-hydroxycinnamic acid. ,, Specifically, 5-FU (∼6 wt %) and pemetrexed (∼18 wt %) were simultaneously loaded into UiO-67-(NH 2 ) 2 ; this MOF showed a pH-dependent release of both drugs in simulated physiological buffers . In addition, commercial BPs were employed recently to generate ALEN-, ZOLE-, and RISE-based coordination complexes and demonstrated suitable pH-dependent degradation, bone affinity [e.g., nano -Ca@ZOLE to hydroxyapatite (HA), 36%, 1 day], and cytotoxicity [e.g., nano -Ca@ALEN, relative cell viability (%RCV) = 38 ± 1% at 7.5 μM in 72 h] against the MDA-MB-231 cell line. However, these BP-based coordination complexes did not lead to porous materials able to encapsulate guest molecules. Furthermore, the reaction of benzene-1,4-bis­(bisphosphonic acid) (BBPA), the BP analogue of benzene-1,4-dicarboxylic acid (BDC), coordinated with Ca 2+ successfully led to BBPA-Ca form I, a 3D framework with channels (7 × 12 Å) large enough to encapsulate and release 5-FU (∼30 wt %) .…”
Section: Introductionmentioning
confidence: 99%
“…The GCMC simulations were conducted by Kotzabasaki et al, and the uptake of gemcitabine was calculated using IRMOF-74-III as an anticancer platform for gemcitabine delivery . GCMC simulation was employed to gain valuable insights into the adsorption behavior of 5-fluorouracil on various MOFs including IRMOF-1, IRMOF-8, IRMOF-10, Mg-MOF74, Fe-MOF74, Cu-MOF74, and Zn-MOF74 . Recent computational studies by our research group have identified MOF-123, MUT-3, and MUT-2 as potential carriers of 5-FU. , Moreover, our research group has evaluated MUT-6 and MUT-7 as candidates for carrying Quercetin …”
Section: Introductionmentioning
confidence: 99%